Analyzing Geotextile as Reinforcement on Road Embankment - Imran, Zariq; Yahya, Nur Faezah (Progress in Engineering Application and Technology, 2021)
Construction of soil embankment on soft soil will cause many problems such as big and non-uniform settlement because of soft soil has less shear strength and high compressibility. Nowadays, soil reinforcement is one of the efficient way for increasing the soil strength and stability of the soil. The usage of geosynthehics especially geotextile has increasing in demand for recent years that can cause decrease of tensile weaknesses and decreasing the settlement of it. The main aim of this paper is to analyze the value of settlement on different location of geotextile that act as reinforcement and different value of loading on the road embankment by using Finite Element Method (FEM). In FEM, the 2D PLAXIS Version 8 software was used in simulating real time of the construction of the embankments starting from distribution of filling work until end of surveillance monitoring data period. The objective of this paper achieved to determine the best location of geotextile on road embankment which was bottom (y=0.00 m) that has minimum value of settlement.